Gambaran Perilaku Hidup Bersih dan Sehat (PHBS) pada Remaja di Kota Depok: Description of Clean and Healthy Living Behavior (PHBS) among Adolescents in Depok City - Saragih, Sukmawati Boru; Rahayu, Ade Ashar; Wibisono, Al Farel Dimas; Salsabillah, Sausan; Al-Fajr, Sayyed Muhammad; Damayanti, Siti (Journal of Public Health Education, 2022)
Introduction: Clean and Healthy Living Behavior (PHBS) is all health behavior that is obtained from the learning process and is practiced based on a person's self-awareness so that individuals, families, groups, and communities can help themselves independently in the health sector and play an active role in achieving improvements in public health. PHBS has 10 indicators, namely, giving birth assisted by health workers, giving exclusive breast milk, weighing toddlers every month, using clean water, washing hands using clean water and soap, using healthy latrines, eradicating larvae at home once a week, eating fruit and vegetables every day, do physical activity every day, and don't smoke at home. Objective: To find out the picture of teenagers’ PHBS in Depok City Methods: This research uses a descriptive quantitative research design to create descriptions, descriptions in a systematic, factual, and accurate manner. The subjects of this research were teenagers in the Depok City area with a total of 780 respondents. Data collection was carried out online, through questionnaire observation (Google form) data was processed and analyzed using Microsoft Word. Results: Based on the behavior of using clean water, 780 (100%) respondents always use clean running water after activities. Based on the behavior of washing hands with soap from 780 respondents which were always 659 (84%), based on the behavior of using healthy latrines from 780 respondents used healthy latrines which was 734 (95%), based on the behavior of eradicating mosquito larvae from 780 respondents which was always 328 ( 42%), based on the behavior of consuming fruit and vegetables from 780 respondents which is always 313 (40%), based on the behavior of doing physical activity every day from 780 respondents which is always 332 (42.5%), based on the smoking behavior of 780 respondents who always as many as 23 (3%), based on the alcohol consumption behavior of 780 respondents which is always as many as 265 (34%). Conclusion: This analysis shows that community behavior in implementing PHBS is good.